Towards a Democratic Coexistence: The Challenge of Re-thinking Citizenly the Education and Management of Two Chilean Schools - Vásquez-Espinoza, Braulio (2024)
Purpose. This article analyzes and discusses the scope, in terms of citizenship learning, that stems from the definitions of ‘management’ provided by two public schools in Chile. Method. The research employed a quantitative methodology with a descriptive scope. The sampling was intentional, involving 73 students, 28 teachers, and 6 assistants. Data were collected through a survey and documentary analysis and were analyzed using SPSS software. Results. Schools primarily based their decisions on a bureaucratic and total quality management approach. Meanwhile, they declared a maximalist conception of citizenship education, but its pedagogical implementation was reduced to fragmented actions with limited participation and an emphasis on results. Conclusions. It is proposed to rethink and transform management processes at both micro and macro levels to facilitate the formation and experience of democratic citizenship in schools. Since these processes mutually influence each other, it is recommended to design proposals with the educational community rather than distancing from it.